Commercial fisheries losses arising from interactions with offshore pipelines and other oil and gas infrastructure and activities. (5th October 2018) - Rouse, Sally; Hayes, Peter; Wilding, Thomas A
Abstract: Interactions between fishing vessels and oil and gas infrastructure can result in damage to fishing gear, loss of fishing time/access, and risks to crew health and safety. The spatial and temporal patterns characterizing previous incidents (and subsequent losses) between fishers and oil and gas infrastructure were quantified and used to identify key risk factors associated with fisheries losses. Between the years 1989 and 2016, 1590 incidents that resulted in a financial loss, vessel abandonment, or an injury/fatality for UK commercial fishers were recorded. The annual number of recorded incidents decreased by 98.6% over a 27-year period. The majority of past incidences resulted in financial losses (rather than injuries or fatalities) and were associated with interactions between single otter trawlers and oil and gas production-related debris. The odds of an incidence occurring varied according to substrate type and fishing intensity. A risk-model for pipeline–fishing interactions in the Fladen Ground showed that there was significant spatial heterogeneity in the risk of an incident along a pipeline according to the angle and intensity of fishing. The results highlight the need to include the full spectrum of potential losses in fisheries impact assessments associated with the installation and decommissioning of oil and gas assets.